Analysis of the Impact of Water Pollution on the Surrounding Environment and Accountability from an Environmental Law Perspective - Vanesa, Audy Angelica; R, Florensia Oktaviani; Wisuta, Ris; Nauli B, Shalom Inka; Ananda, Hauwra; Pasa, Alicia Putri; Hanan, Fadia Zahra; Salwa, Nathasya Atthaya; Nazhimah, Shafira (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Water pollution can be defined as a change in a condition of water reservoir, such as lakes, rivers, seas, and groundwater due to human activities. Modern water pollution occurs as a result of human activities, such as industrial waste, domestic waste, agricultural waste, garbage, and mining activities which contaminate and disrupt the balance of aquatic ecosystems and various aspects of human life. The type of research used is normative-empirical legal research, which involves a case study of normative-empirical legal behavior. The aim of this research is to understand the impact of water pollution on the surrounding environment and the accountability of those responsible for water pollution from an environmental law perspective. Efforts to prevent water pollution are a shared responsibility, requiring cooperation between the government, industries, society, and international organizations.